SINTESIS ABSOLUT ASIMETRIK BARU - Erwin Abdul Rahim (KOVALEN: Jurnal Riset Kimia, 2016)
ABSTRACT New absolute asymmetric syntheses have been found.  Eugenol based-acetylenes monomers have been synthesized, corresponding three compounds and one unknown compound.  Two compounds are crystal chiral (1 and 2) and one (3) not.  Polymerization of chiral crystal and not were different although the structure is same.  After recrystalization polymerization of 1 and 2 compare with 3 also different.  This is one example of new absolute asymmetric synthesis. Keywords : New absolute asymmetric synthesis, eugenol, unknown compound, chiral crystal.